The Use of the Electronic Chart Display and Information System (ECDIS) in the Navigation Process on the MV. Hanwoori - Nesi Natasha Christy; Firdaus Sitepu; Ardhiana Puspitacandri; Iie Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Modern maritime navigation has shifted from conventional methods to integrated electronic systems, where the Electronic Chart Display and Information System (ECDIS) plays a crucial role in improving navigation safety and efficiency. This study aims to analyze the deck officers' understanding level and identify factors that influence the effectiveness of ECDIS use on the MV. Hanwoori. The study employed a qualitative approach with a case study method. The study population was deck officers, with a purposive sampling technique involving the Chief Officer, Second Officer, and Third Officer as informants. Data were collected through structured interviews, direct observation, and documentation, then analyzed using an interactive model of data reduction, data presentation, and conclusion drawing. The results show that ECDIS has been used effectively in route planning and monitoring, but there are still inconsistencies in setting safety parameters, updating ENCs, and managing alarms. These findings indicate that human factors, operational discipline, and technical competence influence system performance. The study's conclusion confirms that although deck officers have a fairly good operational understanding, optimization of safety features and continuous improvement of training are essential to improve navigation safety and minimize human error.